Gramatyčni transformaciji pry hudožn'omu perekladi prozy z horvats'koji movy na ukrajins'ku - Fuderer, Tetyana (Array, 2011)
The paper researches grammar transformations used in literary translations from Croatian into Ukrainian language, and it also endeavours to establish and generalise peculiar grammar characteristics of Croatian and Ukrainian languages, arisen in the process of comparative analysis of original and translated texts.